Analysis of the Symmetries and Conservation Laws of the Nonlinear Jaulent-Miodek Equation - Mehdi Nadjafikhah; Mostafa Hesamiarshad (Abstract and Applied Analysis)
Lie symmetry method is performed for the nonlinear Jaulent-Miodek equation. We will find the symmetry group and optimal systems of Lie subalgebras. The Lie invariants associated with the symmetry generators as well as the corresponding similarity reduced equations are also pointed out. And conservation laws of the J-M equation are presented with two steps: firstly, finding multipliers for computation of conservation laws and, secondly, symbolic computation of conservation laws will be applied.